Analogies constructed by students in a selective high school - Crowley, Julianne Kathleen (Curtin University, 2002)
Research in science education over the past 20 years has emphasized the importance of active cognition in conceptual development. Students formulate knowledge within language constructions constrained by culture and social construction and relate to their own purposes using speech and writing. Many students in high school do not recognize the use of analogy in the development of science theory and concepts. By focusing on the constructed nature of science and analogy this thesis aimed to determine the capacity of high ability students to engage their own thinking and so have a powerful tool with which to deconstruct and reconstruct their scientific understandings. This thesis focused on the use of analogy in a Year 7 electricity unit and a Year 9 geology unit and used examination questions, quizzes, diary entries and interviews to determine the role of analogies in learning. The specific research questions asked were: Can high ability students create their own analogies?, What role do analogies play in learning?, and How do analogies help students in concept development? The thesis found that analogies are powerful tools in supporting student conceptual development. They allow students to link from their existing framework to new understandings and visual analogs were the most effective in supporting learning. The students move to new understandings may not happen within the teaching time but could occur several months after the introduction of the analogy.High ability students are able to recognize and construct their own analogies; however, many students have difficulty deconstructing analogies on their own. The content of the student created analogies seemed to be associated with activities involving reflection and reflection time emerged as a critical component of the learning process. The role of analogies in providing a focus for discussion with peers, teachers and parents so that ideas could be thought about, tested and clarified was found to be one of their important functions in supporting learning.